Scapular Tip Free Flap in Composite Head and Neck Reconstruction. (January 2019) - Tracy, Jeremiah C.; Brandon, Bryan; Patel, Samip N.
Objectives: To describe the use of the scapular tip free flap (STFF) in the reconstruction of head and neck defects. Study Design: Case series with chart review. Setting: Academic medical center. Subjects and Methods: A review of the electronic medical record was performed of all patients who underwent head and neck reconstructive surgery with STFFs from January 1, 2014, through January 1, 2016. Details regarding the disease, defect reconstructed, and surgical outcomes were quantified. Results: Thirty-one consecutive cases were performed at our institution within the period reviewed. The procedures included reconstruction of 5 maxillectomy and 26 mandibulectomy defects. The mean length of mandible reconstructed was 6.8 cm (95% CI, 6.01-7.59; range, 4.0-10.2). Osteotomies were made to contour the scapular bone in 11 cases, including double osteotomies performed in 2 cases. The most common surgical complications were orocutaneous fistula and postoperative hematoma, which occurred in 3 (10%) and 2 (6.5%) of 31 patients, respectively. Conclusion: This series describes a large number of STFFs performed in head and neck reconstruction. The average length of bony defect repair can be significantly larger than what was previously described. Performing osteotomies to the STFF allows for application to anterior mandibular defects. The STFF offers a large soft tissue component, a relatively long pedicle, and acceptable donor site morbidity. The STFF is a versatile reconstructive option that should be considered to address composite defects of the head and neck.